Factors Influencing VNU-IS Students’ Choice of University - Đỗ, Liên Thị Hồng; Nguyễn, Hòa Thị Nhân; Nguyễn, Anh Thị Lan (VNU Journal of Science: Social Sciences and Humanities; Vol 31 No 4, 2015)
The research aims to investigate factors havingimportant impact on students’ choice of university, particularly in the context of Vietnam National University, Hanoi – International School. It was based on the theoretical framework of factors affecting university choice suggested by Chapman (1981). The result from the analysis of variation(ANOVA)showed differences in how each factor is valued by students of various majors and with different fathers’ educational background in selecting VNU-IS. The results from comparing mean and in-depth interview also showed that the VNU-IS unique factors such as educating in foreign languages or IS being owned by VNU, from students’ perspectives, have the most significant impact on why they choose the school to enroll. These findings have been the solid foundation for some recommendations to enhance the rate and the quality of students enrolling in different majors in VNU-IS. Keywords: Educational background, factors affecting choice of university, VNU-IS